Recent developments in Salvia miltiorrhiza polysaccharides: Isolation, purification, structural characteristics and biological activities - Luo, Lei; Xue, Juan; Shao, Zheng; Zhou, Zhang; Tang, Wenqian; Liu, Jinxin; Hu, Hongfei; Yang, Fan (Frontiers in Pharmacology, 2023)
In recent years, natural polysaccharides have attracted more and more attention and research because of their value in the medicine, beauty and food fields. Salvia miltiorrhiza is a traditional Chinese herbal medicine with a history of thousands of years and has antidiabetic, antifibrotic, neuroprotective, antioxidation, anti-inflammatory and other effects. It mainly includes rosmarinic acid, tanshinone I, tanshinone IIA, tanshinone IIB, procatechualdehyde, polysaccharide and salvianolic acids. Salvia miltiorrhiza polysaccharides (SMP) is a polysaccharide extracted and isolated from Salvia miltiorrhiza and has diverse pharmacological effects, such as antioxidation, anti-tumor, hepatoprotective, anti-inflammatory, immune regulatory and cardioprotective effect. In this paper, the research progress of SMP was reviewed from the aspects of extraction, purification, structural characterization and biological activity. We hope to provide a reference for the further development and utilization of SMP.